Budidaya Ikan Lele Kelompok Tani Agape Kelurahan Tuatuka Kecamatan Kupang Timur Kabupaten Kupang - Mikson M. D Nalle; Wahyuni Fanggi Tasik; Yusuf Kamlasi; Ion Tarsardo Sianturi (Journal of Innovation and Applied Technology, 2022)
Community service activities for catfish aquaculture with tarpaulin ponds in Tuatuka, East Kupang District, East Nusa Tenggara Province. The problems are the potential of natural resources that have not been optimized and the desire of the Agape Farmer Group who wants to progress but is constrained by limited knowledge in making ponds, preparation of aquaculture media, stocking larva, maintenance, feeding, monitoring water quality, fish health management and harvesting.